Artificial Intelligence in Precision Agriculture: Advanced Systems for Crop Management and Farm Optimization - Rajnish Jain, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in modern agriculture, revolutionizing traditional farming practices through the integration of advanced technologies and data-driven decision-making systems. This comprehensive article explores the implementation of AI in precision agriculture, focusing on crop management and farm optimization strategies. The article examines various aspects of AI application in agriculture, including precision farming technologies, crop monitoring systems, data analytics, and decision support frameworks. It explores the economic and environmental impacts of these technologies while addressing the challenges and future prospects of AI adoption in agricultural practices. The article highlights how AI-driven solutions are enhancing agricultural productivity through improved resource management, automated monitoring systems, and predictive analytics. The integration of machine learning, computer vision, and Internet of Things (IoT) devices has created sophisticated farming management systems that optimize crop yields while promoting environmental sustainability. This transformation represents a significant advancement in agricultural practices, particularly relevant for addressing global food security challenges and promoting sustainable farming methods in both developed and developing regions.
Keywords: Artificial Intelligence in Agriculture; Precision Farming Technologies; Smart Crop Management; Agricultural Decision Support Systems; Sustainable Farm Optimization